1994
DOI: 10.1073/pnas.91.2.787
|View full text |Cite
|
Sign up to set email alerts
|

Pineal control of aging: effect of melatonin and pineal grafting on aging mice.

Abstract: The pineal hormone melatonin is secreted in all mammals during the dark phase of the circadian cycle (1), but, even more importantly, there are indications that it is a key regulator of aging and senescence (2, 3). The role of melatonin in controlling sexual maturity, sexual cycling, cancer, stress, and the immune response makes it likely that the pineal may be a factor in the syndrome of aging (4)(5)(6). With this in mind, we have administered exogenous melatonin in the drinking water of mice during a fixed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
189
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(198 citation statements)
references
References 28 publications
3
189
0
5
Order By: Relevance
“…8 -10,20 In other studies, long-term treatment with melatonin was followed by an increase of tumor incidence in some mouse strains. [21][22][23] The synthesis of Epitalon with high biologic activity 15 gives a new opportunity for its implementation in clinical practice. It was recently shown that Epitalon increased the life span in 2 strains of fruit flies and in female CBA mice and inhibits the spontaneous tumorigenesis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…8 -10,20 In other studies, long-term treatment with melatonin was followed by an increase of tumor incidence in some mouse strains. [21][22][23] The synthesis of Epitalon with high biologic activity 15 gives a new opportunity for its implementation in clinical practice. It was recently shown that Epitalon increased the life span in 2 strains of fruit flies and in female CBA mice and inhibits the spontaneous tumorigenesis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the observed phenomenon is twofold. On one hand, melatonin has a proposed physiological role in the aging process (Pierpaoli, 1991;Pierpaoli et al, 1991), and decreased secretion of melatonin with aging is documented (Iguchi et al, 1982;Dori et al, 1994). On the other hand, and perhaps of more relevance to our study, there are reports of more profound reductions of melatonin secretion in populations with dementia than in nondemented controls (Souetre et al, 1989;Mishima et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin levels decrease with age [33]. Since melatonin can prolong survival time of mice [2,31] albeit associated with increased spontaneous tumor incidence according to one report [2] -this is likely to be relevant to the aging process [36], even if the exact mechanism is incompletely understood [54]. We have found dietary melatonin can prevent age-related changes in both cerebral mitochondrial function [42] and in levels of production of nitric oxide and reactive oxygen species (ROS) [9].…”
Section: Introductionmentioning
confidence: 99%